ANTILYMPHOCYTE, ANTIMONOCYTE, AND ANTIENDOTHELIAL CELL ANTIBODIES IN CHRONIC-HEMODIALYSIS PATIENTS - (:unkn) unknown (OXFORD UNIV PRESS UNITED KINGDOM, 1992)
Patients receiving chronic haemodialysis treatment are known to have a high prevalence of anti-panel antibodies (anti-lymphocyte, anti-monocyte, and anti-endothelial cell) originating from a number of different possible sensitizing events such as blood transfusions, multiparity, or renal transplantation. In this study the prevalence of these antibodies in 123 chronic haemodialysis patients was evaluated. Anti-lymphocyte antibodies and anti-monocyte antibodies were found in 27.6% and 21.9% of the patient group respectively. Following exclusion of twelve patients within the study population with a history of previous graft rejection, anti-monocyte antibodies were encountered more frequently in transfused patients than those never having been transfused (22.4% versus 0%, P < 0.05), whilst the prevalence of anti-lymphocyte antibodies was similar in both groups (28.2% versus 19.2%). Multiparity, patient age, or duration of dialysis treatment could not be demonstrated to significantly alter the prevalence of either of these antibodies. Of 12 patients with an episode of previous graft rejection, eight were positive for anti-monocyte antibodies and five for anti-lymphocyte antibodies. Anti-endothelial cell antibodies were common in patients in this group, being present in seven of eight individuals investigated.
Keywords: PANEL-REACTIVE ANTIBODIES; CHRONIC HEMODIALYSIS; TRANSFUSION; SENSITIZATION; SENSITIZATION; ALLOANTIGENS; RISK